Pemanfaatan Limbah Serbuk Gergaji Dan Arang Sekam Padi Sebagai Media Sapih Untuk Cempaka Kuning (Michelia Champaca) - Anita Dewi Agustin; Melya Riniarti; Duryat Duryat (Jurnal Sylva Lestari, 2014)
To support the cultivation of yellow cempaka (Michelia champaca) intensively, high quality seedlings was needed. One of the factors that affect the growth and quality of seedling was growth media. The objectives of the research were to (1) determine the effect of saw dust and rice husk as growth media than the top soil for yellow cempaka seedlings; (2) obtained the best composite media between top soil with saw dust and rice husk as media for growth media for yellow cempaka seedlings. The research was conducted in greenhouse, started from January to April 2013. The experiment used Completely Randomized Design (CRD) with 6 treatments and 3 replicates, every experiment unit consisted of 6 yellow cempaka seedlings so the total number amounted to 108 seedlings. The treatment were number of medias (1) top soil; (2) saw dust; (3) rice husk; (4) top soil + saw dust 1:1; (5) top soil + rice husk 1:1; (6) top soil + saw dust + rice husk 1:1:1. Observed variables include high growth, diameter, number of leaves, root length, top root ratio, total dry weight and seedling quality index. The results showed that growth media of rice husk gave a good growth of yellow cempaka same as media top soil. Composite growth media that had a better growth of yellow cempaka seedling was composite growth media top soil + rice husk 1:1. Keywords: organic matter, rice husk, growth media, saw dust, yellow cempaka